2007
DOI: 10.1007/s10353-006-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster bomb vs. antipersonnel mine related injuries. An experience from the Kuwaiti-Iraqi border from June 1998 to November 2000

Abstract: Zusammenfassung. Grundlagen: Seit dem letzten Jahrzehnt kommen auf den Schlachtfeldern in aller Welt die Submunition enthaltenden Cluster Bombs (SB) zum Einsatz. Sie stellen somit eine neue Herausforderung fü r die Kriegschirurgie dar.Methodik: 32 Patienten wurden entweder durch Antipersonen-Minen (AP) oder SB verletzt und in einem Feldspital behandelt. Das Verletzungsmuster wurde mittels der Klassifikation des internationalen Komitees vom Roten Kreuz und mittels Gustilos Klassifikation fü r offene Frakturen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…22 More men were injured or killed by landmines or UXO than were women (0-30•6% women) (appendix pp 5-6). 13,16,[19][20][21][22]25,[28][29][30]33,36,38,41,42,46,50,51,53,55,56,58,[60][61][62]63,65 The mean ages of casualties (range 18•5 years to 38•1 years) in all included studies falls into the economically productive age range (15-64 years). 16,17,25,28,30,33,38,46,50,53,57,[55][56][57][58][59][61][62][63] This finding matches with the type of activity that the victim was doing at the time of injury and the economic effect on victims and their families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 More men were injured or killed by landmines or UXO than were women (0-30•6% women) (appendix pp 5-6). 13,16,[19][20][21][22]25,[28][29][30]33,36,38,41,42,46,50,51,53,55,56,58,[60][61][62]63,65 The mean ages of casualties (range 18•5 years to 38•1 years) in all included studies falls into the economically productive age range (15-64 years). 16,17,25,28,30,33,38,46,50,53,57,[55][56][57][58][59][61][62][63] This finding matches with the type of activity that the victim was doing at the time of injury and the economic effect on victims and their families.…”
Section: Resultsmentioning
confidence: 99%
“…60 Four studies 17,19,22,63 reported higher case fatality ratios for children injured by landmines or UXO than for adults, whereas two 20,51 reported higher case fatality ratios for adults than for children (appendix p 8). The proportion of casualties of landmines or UXO younger than 18 years ranged from 22% to 55% across twelve studies; 13,14,16,17,20,25,28,33,46,50,53,[58][59][60]62,63,65 Landmines resulted in more amputations from the hip to the foot than did UXO (21•7% caused by landmines vs 5•5% caused by UXO in one study; 65 29•2% vs 8•1% in another 63 ), whereas UXO caused more amputations relating to the arms, upper body, and head than did landmines (27•8% caused by UXO vs 8•7% caused by landmines in one study; 65 22•1% vs 6•5% in another 63 ). Children were more likely to be injured by UXO than were adults in five studies.…”
Section: Resultsmentioning
confidence: 99%
“…During armed conflict civilian victims suffer not only from the direct effects of military weaponry, but also due to a breakdown of civilian medical institutions [19] and the lack of safe means of evacuation to and from hospitals in the conflict zone. As a result, these patients appear hours to many days later at medical institutions that were hastily set up and that serve as first treatment point and triage place.…”
Section: Discussionmentioning
confidence: 99%
“…Victims should also receive rehabilitation services, including mental health care and physiotherapy. Many of these services are unavailable or scarce in conflict zones, and the added burden of these patients can overwhelm an already strained health system, especially in post-conflict settings 12,13 . Victims also need assistance with integration back into society.…”
Section: Caring For Victimsmentioning
confidence: 99%